The use of Communicative Language Learning (CLL) to Teach Speaking at a Taiwanese Elementary School: Implementation and Students’ Responses - Laura Yosephine Tan; Listyani Listyani (UIN Salatiga, 2020)
Speaking is one of the important skills to master. The importance of learning speaking skills helps people to share their ideas, agreement or disagreement, compliment, and so on to others. Some students feel a lack of practice in learning English because they don't have enough support, including those in Taiwan. Therefore, the purpose of the study is to investigate how Taiwanese teachers apply CLL in speaking activities and the students' responses towards speaking activities which implement CLL at an elementary school in Taiwan. Data for this qualitative study were gathered from semi-structured interviews and reflective journals. The participants were one Taiwanese English teacher and 32 elementary school students. Data from the semi-structured interview were recorded, then transcribed. After that, themes were drawn based on the transcribed interviews. Based on the data, it was found that the Taiwanese English teacher applied CLL to teach the English language. Some activities such as group discussion and Think-Pair-Share were done. These activities were found useful because students could gain more vocabulary, a fun atmosphere created inside the classroom, and better fluency and pronunciation.